Galvanic replacement reaction to prepare catalytic materials. (2nd November 2022) - Hong, Yongju; Venkateshalu, Sandhya; Jeong, Sangyeon; Tomboc, Gracita M.; Jo, Jinhyoung; Park, Jongsik; Lee, Kwangyeol
Abstract: Galvanic replacement reaction (GRR) has gained considerable interest as a facile and versatile synthetic method for modulating compositions, morphologies, and corresponding physicochemical properties of metallic nanoparticles. Thus far, extensive knowledge of GRR on monometallic templates has been accumulated, backed with ample experimental data and computational modeling and validation. The GRR templates have recently been extended to other materials such as alloys, oxides, sulfides, and liquid metals. These new materials have demonstrated potential applications in electrochemical energy conversion systems, which have been relatively unexplored for GRR‐originated materials. In this review, the recent findings in GRR on these new template materials are introduced, pointing to the incredible versatility of the GRR methodology in diversifying the catalytic materials classes. We further discuss the remaining critical issues and future research directions of GRRs to fully exploit the potential of GRR in spearheading future advances in electrocatalytic energy conversion and other important applications. Abstract : Recent advances in galvanic replacement reaction beyond the monometallic templates have been addressed, showcasing fine compositional and morphological control with diverse types of GRR templates. A comprehensive list of applicational studies on GRR‐based nanoparticles is also provided.